2024
DOI: 10.1021/acsomega.3c07560
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on the Boosted Effects of Anion Vacancy in the Heterogeneous Photocatalytic Degradation, Part II: Focus on Oxygen Vacancy

Mahdieh Rezaei,
Alireza Nezamzadeh-Ejhieh,
Ahmad Reza Massah

Abstract: Environmental problems, including the increasingly polluted water and the energy crisis, have led to a need to propose novel strategies/methodologies to contribute to sustainable progress and enhance human well-being. For these goals, heterogeneous semiconducting-based photocatalysis is introduced as a green, eco-friendly, cost-effective, and effective strategy. The introduction of anion vacancies in semiconductors has been wellknown as an effective strategy for considerably enhancing the photocatalytic activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 316 publications
(647 reference statements)
0
3
0
Order By: Relevance
“…For example, a summarized study has been published on the effects of OV-based metal oxide photoanodes for application in the photocatalytic water splitting process . The vital roles of vacancy engineering in boosting solar-driven photocatalysis activity have also been reviewed. , Some reviews studied various vacancy defects categories of the vacancy-engineered photocatalysts fabrication, the characterization techniques, and the vacancy defects roles in various photocatalytic fields, including water splitting, photodegradation of organic compounds, CO 2 conversion, generation of hydrogen peroxide, and N 2 fixation. In 2023, we illustrated the functions, synthesis, characterization procedures, and applications of semiconductors mediated with O, N, S, and halogen vacancies in the photocatalytic degradation process. , Despite a recent clear upward trend in the number of research studies on SV photocatalysts, there are few relevant overviews on the mechanism and application of SV photocatalysts. The SV generation methods via various synthetic routes and the quality of SV creation during the synthesis procedures were studied by multiple researchers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a summarized study has been published on the effects of OV-based metal oxide photoanodes for application in the photocatalytic water splitting process . The vital roles of vacancy engineering in boosting solar-driven photocatalysis activity have also been reviewed. , Some reviews studied various vacancy defects categories of the vacancy-engineered photocatalysts fabrication, the characterization techniques, and the vacancy defects roles in various photocatalytic fields, including water splitting, photodegradation of organic compounds, CO 2 conversion, generation of hydrogen peroxide, and N 2 fixation. In 2023, we illustrated the functions, synthesis, characterization procedures, and applications of semiconductors mediated with O, N, S, and halogen vacancies in the photocatalytic degradation process. , Despite a recent clear upward trend in the number of research studies on SV photocatalysts, there are few relevant overviews on the mechanism and application of SV photocatalysts. The SV generation methods via various synthetic routes and the quality of SV creation during the synthesis procedures were studied by multiple researchers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Fe 3+ can be reduced to Fe 2+ by electrons on the conduction band (CB) of α-Fe 2 O 3 , thus reducing the loss of Fe 2+ and the generation of solid sludge . Nevertheless, the single α-Fe 2 O 3 photocatalyst still exhibited poor photocatalytic activity due to the slow migration kinetics and separation of photogenerated carriers. , It is shown that the construction of heterojunctions can effectively improve the separation efficiency of photogenerated carriers and enhance the catalytic activity of photocatalysts. Particularly, heterostructures with more interfacial regions shorten the charge transfer distance and time, thereby improving the photocatalytic activity, which leads to high-rate capability and efficient catalytic activities . The emerging superlattice structure is laminated composites formed by alternating growth of thin layers of different materials .…”
Section: Introductionmentioning
confidence: 99%
“…For example, various types of AV defects, the synthesis procedures for vacancy-engineered photocatalysts for water splitting, etc. have been discussed in a review by Ding et al In 2023, we collected and discussed the functions, synthesis methods, and applications of semiconductors mediated with O, N, S, and halogen vacancies in PC degradation. , …”
Section: Introductionmentioning
confidence: 99%